FEATURES OF USING FIRST-ORDER CONVERTED MEASUREMENT KALMAN FILTER FOR polar coordinates AND DOPPLER FREQUENCY MEASUREMENTS - A. A. Mikhalkovski; A. S. Solonar (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Features of converted measurement Kalman filter implementations for polar coordinates and Doppler frequency measurements from radar survey are considered. The estimation performance of converted measurement Kalman filter modifications is compared.